2013
DOI: 10.1364/ol.38.000923
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts in polarization-sensitive optical coherence tomography caused by polarization mode dispersion

Abstract: Polarization Mode Dispersion (PMD) severely degrades images of biological tissue measured with polarization sensitive Optical Coherence Tomography (PS-OCT). It adds a bias to the local retardation value that can be spatially confined, resulting in regions of seemingly high sample birefringence that are purely artificial. Here, we demonstrate and analyze this effect, both experimentally and with numerical simulations, and show that artifacts can be avoided by limiting the system PMD to less than the system axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 11 publications
0
44
0
Order By: Relevance
“…Recent studies have suggested that polarization mode dispersion (PMD) increases polarimetric noise in PS-OCT [35,36]. Some methods have been developed to overcome this issue using various approaches [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that polarization mode dispersion (PMD) increases polarimetric noise in PS-OCT [35,36]. Some methods have been developed to overcome this issue using various approaches [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Following the finding that polarization mode dispersion in the OCT interferometer and catheters inhibits accurate and reproducible polarimetry [107], methods were identified to mitigate this effect and enable intravascular birefringence [108,109] and depolarization [110] measurements. This work has recently been translated into clinical studies with intriguing results demonstrating the very promising utility of polarimetry for vascular and plaque characterization [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In fiber-based PS-OCT systems, PMD 40 in fiber and optical components, such as the circulator, are believed to contribute to the polarimetric noise in the birefringence measurement, 41,42 and approaches have been proposed to compensate for the PMD introduced by SMF and other optical components. 43 Structural properties of tissue also contribute to polarimetric noise.…”
Section: Discussionmentioning
confidence: 99%